Maximum Spanning Tree Graph Model: National Examination Data Analysis of Junior High School in Lampung Province - Maskar, Sugama (Proceeding International Conference on Science and Engineering, 2020)
The purpose of this study is to determine the tendencies of learning in Lampung Province especially at junior high school level. Subjects of this study are all result of national examination data for junior high school in 2017 and 2018 in Lampung Province. The method of this study using model analysis of maximum spanning tree (MST) graph assisted by descriptive and inferential statistics technique. The data obtained are analysed using descriptive statistical analysis to find out the basic information of the data and inferential statistical analysis to get the value of coefficient correlation. Then, the MST graph is formed using Kruskal’s algorithm by interpreting the vertices as a subject and the edges as the value of coefficient correlation. The subject that have the closest relationship to any subject is a graph vertex with the greatest degree. Based on the MST graph model, the result of this study shows that the subject which has closest relationship with another subject is Science in 2017, while in 2018 are English and Mathematics. Based on these result and relevant research, the conclusion shows that Science and Mathematics to be the centre for the national examination of junior high school in 2017 and 2018 in Lampung Province.